HEALTH LOCUS OF CONTROL ON COPING MECHANISMS OF CHRONIC RENAL FAILURE PATIENTS WITH HEMODIALYSIS THERAPY AT BLAMBANGAN HOSPITAL BANYUWANGI - Ninis indriani indriani; Fransiska Erna Damayanti; Iftitah Saily Zakiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background: Patients with chronic kidney failure (CKD) require hemodialysis therapy for a long time which can cause patients to experience stress. Stressful conditions in patients with CKD affect coping mechanisms. One that affects the coping mechanism of people with CKD is belief (locus of control). Purpose: This study aimed to determine the correlation between the health locus of control and the coping mechanisms of CKD patients undergoing hemodialysis. Method: The type of research used was a correlation study with a cross-sectional research design. The total sample is 88 respondents with a purposive sampling technique. Data collection used the MHLCS (Multidimensional Health Locus of Control Scale) questionnaire and the Jalowiec Coping Scale. Data were analyzed using the Fisher's Exact test. Results: This study showed that almost all respondents have a high health locus of control with coping mechanisms; most of the respondents fall into the adaptive category. The data analysis showed a significant correlation between health locus of control and coping mechanisms in CRF patients on hemodialysis therapy. Conclusion: Hemodialysis patients with high health locus of control have adaptive coping mechanisms. For respondents to remain in adaptive coping, spiritual activities are needed to guide people with CKD so that they are much more willing to accept their health conditions sincerely. Keywords: Chronic kidney failure; hemodialysis; Health locus of control; coping mechanisms